Upaya Peningkatan Keterampilan Berbahasa Inggris Melalui Program Outing Class - Heni Novita Sari; Siti Ithriyah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
English language skills are not only obtained through learning activities in lectures, but also through outing class programs. The focus of the outing class is a visit to the National Museum accompanied by several foreign guide. The purpose of this outing class program is to find out the history of the National Museum, to provide insight into English for Tourism, and to improve the students' skills in speaking English with Foreign guide. The main problems are as follows: 1) The ability to speak English is lacking in practical training, 2) The importance of improving English language skills, and 3) The low access to develop the students’ skills in English. This activity is a community partnership program activity involving foreign guide partners located at the National Museum. This service is carried out using the methods 1) Discussions and lectures, 2) Education, and 3) English communication assistance with foreign guide. The results of this activity show the high enthusiasm of students in participating in this outing class program. This outing class program is a positive activity as an effort to improve the students' skills in English.